THE USE OF PQRST (PREVIEW, QUESTION, READ, STATE, TEST) IN TEACHING READING NARRATIVE TEXT FOR EIGHT GRADERS STUDENTS OF SMPN 2 PURWOASRI - Abdillah, Zamratus Zahra (FKIP UNISKA, 2020)
PQRST (Preview, Question, Read, State, and Test) Method is alternative method to make teaching and learning process interesting. Through PQRST method, the students can participate in the teaching and learning process actively. PQRST method is expected to be effective because the use of it can avoid the weakness of common method that be used in teaching and learning process. The research design used is quantitative and the method is one group pre-test and post-test experimental design. In this study, the data are collected from the result of pre-test and post-test. After getting result of score between pre-test and post-test, the data was couted by using SPSS to find t-test. It is used to describe whether there is significant difference between students' reading narrative text before and after being taught by using PQRST method. It is recommended for the teacher to use PQRST method. It can help them to develop their teching method, especially in teaching reading narrative text. It also recommended for the reader this research hopefully can add the new knowledge which they have not been known before and the last for the further researcher this research hopefully can give new information and references in doing same kind research, and they can improve this research to be complete and better.